Delay Patterns and Associated Factors Among Gastric Cancer Patients Visiting Tertiary Hospital in Ethiopia - Tsegab Alemayehu; Semira Abdelmenan; Hailu Wondimu; Segni Kejela; Firaol Dandena; Tesfahun Ali; Zewdu Abadi; Zekarias Seifu (Cancer Reports)
ABSTRACT Background Gastric cancer ranks sixth in terms of incidence and fifth in terms of mortality in the world. It is also the fifth most frequent cancer in Ethiopia. In developed countries such as Japan, the diagnosis of gastric cancer is made early and has a better prognosis, but in developing countries like Ethiopia, the majority of patients present late in the advanced state. This study assessed delay patterns and associated factors among gastric cancer patients in Tikur Anbessa Specialized Hospital in Ethiopia. Methods A single‐center cross‐sectional study was conducted on 64 gastric cancer patients on follow‐up from February 2021 to March 2023. The main outcome measures are the mean length of total delay, patient delay, diagnosis delay, and treatment delay. SPSS software version 26 and the Mann–Whitney statistical test were used to verify associations between the time intervals of access to treatment and socioeconomic factors, clinical variables, and patient‐reported reasons, adopting a 0.05 significance level. Results In this study, the mean length of patient delay was 106 (SD = 142) days, the diagnosis delay was 318 (SD = 370) days, and the treatment delay was 43 (SD = 43) days. The average length of the total delay between symptom onset and definitive treatment was 467.4 (SD = 396.3) days. The greater length of patient delay in this study was correlated with lack of awareness (p < 0.001), search for traditional alternatives (p value 0.02), rural residence (p = 0.05), and economic hindrances (p = 0.01), and diagnosis delay was correlated with misdiagnosis (p < 0.001). Conclusion and Recommendation Delays among gastric cancer patients in this study are much greater than those seen in other low‐income countries. Patient delay and diagnosis delay have a lion's share in the breakdown of the delays in our setup. Lack of awareness, the search for traditional alternatives, economic hindrances, and misdiagnosis were associated factors for delays. We recommend training primary healthcare providers regarding early signs of gastric cancer and integrating community‐based public health interventions to increase awareness of cancer and early health‐seeking behaviors. Along with increasing oncologic centers both by numbers and by quality of services.